Building a transformative initiative for a territorialized agri-food system: constructing a living-lab and confronting norms? A case study from Mirecourt (Vosges, France). (December 2021) - Fèche, R.; Noûs, C.; Barataud, F.
Abstract: The change of scale and potential reconfiguration of decision-making powers make the French context of reterritorialization of food seem favorable to the transition of agri-food systems in certain areas. However, it also includes a movement towards normalization and integration into the dominant system, which may lower the goals of transition, through the norm conveyed by actors and systems. Based on the example of a rural territory in the Vosges and a multi-actor agri-food dynamic in which the authors of this article are stakeholders, our analysis shows that a territorialized agri-food dynamic can actually create new narratives and new ways of doing and thinking that are necessary for the transition. This is achieved by at least partially standing back from this context and drawing on different resources. The search for otherness, both in the content and in the form of the project, is an advantage for a real transition of the agri-food system, without however guaranteeing it. Periods of reassurance shielded from the dominant regime and allowing for collective experimentation with alternative initiatives, as well as the reflexivity of the actors involved throughout the simultaneous processes of reflection and action, afford some distance from the normalizing context while taking advantage of the resources it can offer. The living-lab approach constitutes an inspiring methodology to achieve this. It allows for the implementation of an otherness of content and supports an otherness of form by facilitating the emergence of a niche in the food governance of the territory. At the same time, it also promoted a collective reflexivity among the stakeholders involved. Highlights: The agri-food systems transition seems to be necessary at different scales. It is part of a re-territorialisation of these issues. Normalization and integration to the dominant system presents a risk of reducing the ambitions of the transition. Norms conveyed by actors and devices contribute to this process. An alterity, both on the project substance and form, is an advantage for a true transition of the agri-food system. Times of reinsurance that are protected from the dominant regime are therefore needed. These times allow for collective experimentation with alternative initiatives and reflexivity. Living-lab approach provides an inspiring methodology to achieve this.